The Roles of Epigenetics in the Interplay Between Beneficial Rhizobacteria and Plants - Rui Zou; Zhihui Lu; Armin Djamei; Friedrich Kragler; Hon‐Ming Lam; Shoudong Zhang (Modern Agriculture)
ABSTRACT Plant growth‐promoting rhizobacteria (PGPR) are beneficial soil bacteria that can enhance crop growth and health through various mechanisms, including nutrient acquisition, hormone production, and induced systemic resistance. Epigenetic modifications of plants play crucial roles in the effects of PGPR on plant growth and health by regulating gene expression patterns that can modify plant architecture including root architecture, enhance abiotic/biotic stress tolerance, optimise nutrient use, and influence hormonal pathways. Understanding these epigenetic dynamics can pave the way for developing more effective biofertilizers and sustainable agricultural practices. In this review, we will discuss recent advances in understanding the relationship between PGPR and crop plants, with special focus on how epigenetics including DNA methylation, histone modifications and noncoding RNA play a key role in the complex interplay between them.